Preparation and characterization of lignosulfonate grafted layered double hydroxides and their applications as anti-ultraviolet additives for bitumen. (20th January 2019) - He, Bianyang; Yu, Jianying; Du, Wei; Cao, Zhilong; Han, Xiaobin
Highlights: LS grafted LDHs were prepared by grafting of hydroxyl groups via covalent linked by isocyanate group of diisocyanate. LS grafted LDHs had a combined effect of chemically absorbing and physically reflecting UV light on bitumen. LS grafted LDHs exhibited better improvement than LDH on anti-UV aging of bitumen. Abstract: Lignosulfonate (LS) grafted layered double hydroxides (LDHs) were prepared through covalent bonding with diisocyanate (diphenyl-methane-diisocyanate (MDI), toluene-2, 4-diisocyanate (TDI) or isophorone diisocyanate (IPDI)), and were characterized by Fourier transform infrared (FTIR) spectrometer, X-ray diffraction (XRD), scanning electron microscopy (SEM) and ultraviolet and visible (UV–vis) spectroscopy. The degree of grafting (Dg ) and mass proportion (Mp ) had also been calculated. Then LS grafted LDHs modified bitumen was investigated using high temperature storage stability, physical properties measurement and thin-layer chromatography with flameionization detection test. FTIR and XRD showed that LS was successfully grafted to LDHs via covalent linked by diisocyanate. SEM displayed that LS grafted LDHs represented a stable cross-linked structure and had weaker surface agglomeration compared to LDHs. Dg and Mp of LS grafted LDHs linked by MDI (LS-m-LDHs) respectively reached up to 71.68% and 2.53:1, representing excellent grafting effect. The UV–vis analyses displayed that LS grafted LDHs had better UV absorbing ability than LDHs, which had a combined effect of chemically absorbing and physically reflecting UV light. Storage stability test expressed that the compatibility between bitumen and LDHs was improved prominently by the grafting of LS. Before and after aging, the variations of retained penetration ratio (RPR), ductility retention rate (DRR), softening point increment (SPI), viscosity aging index (VAI) and the colloid stable index (CI ) of LS grafted LDHs modified bitumen were smaller compared to LS modified bitumen and LDHs modified bitumen, which illustrated that LS grafted LDHs exhibited better anti-UV aging ability of bitumen in comparison with LDHs and LS. In improving the aging resistance of bitumen. LS-m-LDHs were superior to LS grafted LDHs linked by TDI and LS grafted LDHs linked by IPDI.